Gallium and indium co-doping effects on structural, optical and luminescence properties of ZnO nanostructures. (June 2021) - Seid, Endris Taju; Dejene, Francis B.
Abstract: Doped ZnO nanoparticles were synthesized using sol-gel method, with simultaneous incorporation of Gallium (Ga) and Indium (In). The structural, chemical, optical an luminescence properties of the pure, single doped and co-doped (GaInZnO) nanostructures were characterized by X-Ray diffraction (XRD), EXD Field Emission Scanning Electron Microscopy (FESEM), UV–vis spectroscopy, and Photoluminescence spectroscopy. XRD disclosed that the produced nanostructures were pure and single phase hexagonal wurtzite in structure. The diffraction peaks of the co-doped sample was seen to shift slightly towards lower diffraction angle values as compared to pure ZnO. The calculated crystallite sizes significantly varied between 21.9 and 8.2 nm depending on the dopant ratios. All synthesized samples show excellent optical properties with more than 85 % reflectance in the visible region. The energy band gap of the crystals were observed to shrink with co-doping than undoped and single doping. The PL results also revealed the typical UV and visible emission band patterns with a slight shift to the lower wavelength for the co-doped samples. The proper co-doping of In and Ga is therefore expected to provide a broad range optical and physical properties of ZnO nanostructures for a variety of optoelectronic applications.